An expression such as $\sqrt{2}$, $\sqrt[3]{4}$, $\sqrt{a+b}$ that exhibits a radical sign, is referred to as a "radical". The word Radical is derived from the Latin word "radix" which means "root". The radical symbol ($\sqrt{}$), is used to indicate the square root or $n^{th}$ root.The number inside the radical are called as **Radicand. **

For example:

The condition under which radicals can be added or subtracted are much the same as the condition for letters in an algebraic expression. The like radicals can be add or subtract. If the radicals are unlike radicals, try to simplify one or both of the radicals.

For example: $\sqrt{2} + \sqrt{5}$ cannot be added.

$\sqrt{3} + \sqrt[3]{3}$ cannot be added.**Definition:** A radical is the principal $r^{th}$ root of k where r is a positive integer greater than one and k ia a real number.

The operation of the radicals are opposite to the exponents.

For example: $\sqrt[r]{k}$ in this case r is called as index, âˆš is called as radical sign, and k is called as radicand.

Related Calculators | |

Adding Radicals Calculator | Adding and Subtracting Polynomials Calculator |

Adding and Subtracting Rational Expressions Calculator | Adding Integer |

Below are the steps for simplifying the add and subtract radicals.

1) The sum or difference of the reduced radicals can be obtained by adding or subtracting their co-efficient.

2) Remember only like radicals can be add or subtract.

3) If the radicals are unlike radicals, try to simplify one or both of the radicals.

4) Once the radicals are simplified, add or subtract the numbers directly preceding the radicals that are same.### Solved Examples

**Question 1: **Simplify 4 $\sqrt{5}$ + 6$\sqrt{5}$ - 2$\sqrt{5}$

** Solution: **

Given 4 $\sqrt{5}$ + 6 $\sqrt{5}$ - 2 $\sqrt{5}$

= 10 $\sqrt{5}$ - 2 $\sqrt{5}$

= 8 $\sqrt{5}$

**Question 2: **2 $\sqrt{3}$ + 6$\sqrt{3}$ - 3 $\sqrt{3}$

** Solution: **

Given 2 $\sqrt{3}$ + 6$\sqrt{3}$ - 3 $\sqrt{3}$

= 8 $\sqrt{3}$ - 3 $\sqrt{3}$

= 5 $\sqrt{3}$

**Question 3: **12 $\sqrt{5}$ + 7 $\sqrt{5}$ + 2 $\sqrt{5}$

** Solution: **

Given 12 $\sqrt{5}$ + 7 $\sqrt{5}$ + 2 $\sqrt{5}$

= 19 $\sqrt{5}$ + 2 $\sqrt{5}$

= 21$\sqrt{5}$

**Question 4: **2 $\sqrt{75}$ + 4$\sqrt{3}$ - 8$\sqrt{27}$

** Solution: **

Given 2 $\sqrt{75}$ + 4 $\sqrt{3}$ - 8 $\sqrt{27}$

= 2 $\sqrt{25 \times 3}$ + 4 $\sqrt{3}$ - 8 $\sqrt{9 \times 3}$

= 2 $\times$ 5 $\sqrt{3}$ + 4 $\sqrt{3}$ - 8 $\times$ 3 $\sqrt{3}$

=10 $\sqrt{3}$ + 4 $\sqrt{3}$ - 24 $\sqrt{3}$

= 14 $\sqrt{3}$ - 24 $\sqrt{3}$

= -10 $\sqrt{3}$

Two or more radical expressions are called as like radicals if they have the same index and the same radicand.

Two radical expressions that are like radicals can be added or subtracted by adding or subtracting their coefficients.

### Solved Examples

**Question 1: **17 $\sqrt{7}$ + 4 $\sqrt{7}$ - 12 $\sqrt{7}$

** Solution: **

Given 17 $\sqrt{7}$ + 4 $\sqrt{7}$ - 12 $\sqrt{7}$

= 21 $\sqrt{7}$ - 12 $\sqrt{7}$

= 9 $\sqrt{5}$

**Question 2: **8 $\sqrt{32}$ - 3 $\sqrt{18}$ + 2 $\sqrt{3}$

** Solution: **

Given equation is

8 $\sqrt{32}$ - 3 $\sqrt{18}$ + 2 $\sqrt{3}$

= 8 $\sqrt{16 \times 2}$ - 3 $\sqrt{9 \times 2}$ + 2 $\sqrt{3}$

=8 $\times$ 4$\sqrt{2}$ - 3 $\times$ 3 $\sqrt{2}$ +2 $\sqrt{3}$

= 32 $\sqrt{2}$ - 9 $\sqrt{2}$ + 2 $\sqrt{3}$

= 23 $\sqrt{2}$ + 2 $\sqrt{3}$

**Question 3: **2 $\sqrt{25}$ - 3 $\sqrt{80}$ + 3 $\sqrt{36}$

** Solution: **

Given 2 $\sqrt{25}$ - 3 $\sqrt{80}$ + 3$\sqrt{36}$

= 2 $\times$ 5 - 3 $\times$ 4 $\sqrt{5}$ + 3 $\times$ 6

= 10 - 12 $\sqrt{5}$ + 18

= 28 - 12 $\sqrt{5}$

= 4 [ 7 - 3 $\sqrt{5}$ ]

**Question 4: **4x $\sqrt{25}$ - 3x $\sqrt{80}$ + 2x $\sqrt{36}$

** Solution: **

Given 4x $\sqrt{25}$ - 3x $\sqrt{80}$ + 2x $\sqrt{36}$

= 4x $\times$ 5 - 3x $\times$ 4 $\sqrt{5}$ + 12x

= 4x - 12x $\sqrt{5}$ + 12x

= 16x - 12x $\sqrt{5}$

= 4x [ 4 - 3 $\sqrt{5}$ ]

1) The sum or difference of the reduced radicals can be obtained by adding or subtracting their co-efficient.

2) Remember only like radicals can be add or subtract.

3) If the radicals are unlike radicals, try to simplify one or both of the radicals.

4) Once the radicals are simplified, add or subtract the numbers directly preceding the radicals that are same.

Given 4 $\sqrt{5}$ + 6 $\sqrt{5}$ - 2 $\sqrt{5}$

= 10 $\sqrt{5}$ - 2 $\sqrt{5}$

= 8 $\sqrt{5}$

Given 2 $\sqrt{3}$ + 6$\sqrt{3}$ - 3 $\sqrt{3}$

= 8 $\sqrt{3}$ - 3 $\sqrt{3}$

= 5 $\sqrt{3}$

Given 12 $\sqrt{5}$ + 7 $\sqrt{5}$ + 2 $\sqrt{5}$

= 19 $\sqrt{5}$ + 2 $\sqrt{5}$

= 21$\sqrt{5}$

Given 2 $\sqrt{75}$ + 4 $\sqrt{3}$ - 8 $\sqrt{27}$

= 2 $\sqrt{25 \times 3}$ + 4 $\sqrt{3}$ - 8 $\sqrt{9 \times 3}$

= 2 $\times$ 5 $\sqrt{3}$ + 4 $\sqrt{3}$ - 8 $\times$ 3 $\sqrt{3}$

=10 $\sqrt{3}$ + 4 $\sqrt{3}$ - 24 $\sqrt{3}$

= 14 $\sqrt{3}$ - 24 $\sqrt{3}$

= -10 $\sqrt{3}$

Two radical expressions that are like radicals can be added or subtracted by adding or subtracting their coefficients.

Given 17 $\sqrt{7}$ + 4 $\sqrt{7}$ - 12 $\sqrt{7}$

= 21 $\sqrt{7}$ - 12 $\sqrt{7}$

= 9 $\sqrt{5}$

Given equation is

8 $\sqrt{32}$ - 3 $\sqrt{18}$ + 2 $\sqrt{3}$

= 8 $\sqrt{16 \times 2}$ - 3 $\sqrt{9 \times 2}$ + 2 $\sqrt{3}$

=8 $\times$ 4$\sqrt{2}$ - 3 $\times$ 3 $\sqrt{2}$ +2 $\sqrt{3}$

= 32 $\sqrt{2}$ - 9 $\sqrt{2}$ + 2 $\sqrt{3}$

= 23 $\sqrt{2}$ + 2 $\sqrt{3}$

Given 2 $\sqrt{25}$ - 3 $\sqrt{80}$ + 3$\sqrt{36}$

= 2 $\times$ 5 - 3 $\times$ 4 $\sqrt{5}$ + 3 $\times$ 6

= 10 - 12 $\sqrt{5}$ + 18

= 28 - 12 $\sqrt{5}$

= 4 [ 7 - 3 $\sqrt{5}$ ]

Given 4x $\sqrt{25}$ - 3x $\sqrt{80}$ + 2x $\sqrt{36}$

= 4x $\times$ 5 - 3x $\times$ 4 $\sqrt{5}$ + 12x

= 4x - 12x $\sqrt{5}$ + 12x

= 16x - 12x $\sqrt{5}$

= 4x [ 4 - 3 $\sqrt{5}$ ]

More topics in Adding and Subtracting Radicals | |

Adding Radicals | Subtracting Radicals |

Related Topics | |

Math Help Online | Online Math Tutor |